Precomputation Based Adaptive QOS Routing With Bandwidth Quarantees - Lim , Sing King (2004)
This thesis presents a new routing algorithm for adaptive Quality of Service (QoS) routing of bandwidth quaranteed tunnels using a precomputattion approach. Bandwidth guaranteed routing is useful for applications that cannot adapt to inconsistent service levels such as the delivery of multimedia traffic. Precomputation schemes, on the other hand, attempt to reduce the set-up delay and the overheads of adaptive route computation by reusing a path for multiple flow requests. In order to accomplish this, path precomputatin introduces a trade-off between processing overhead and the quality of the routing decisions.